Pengaruh Terapi Olahraga Yoga Terhadap Psikososial Lansia di Posyandu Kawan Seiring Wilayah Kerja Puskesmas Rejosari - Sherly Mutiara; Ftr.Dewi Sepi Yanti (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
This study aims to evaluate the effect of yoga therapy on the psychosocial aspects of elderly individuals at the Kawan Seiring Posyandu within the working area of Puskesmas Rejosari. Elderly individuals often face various psychosocial challenges, such as decreased social interaction, stress, and low life satisfaction, which can affect their quality of life. The research method employed an experimental design with a pre-test and post-test approach involving 30 elderly participants who engaged in a yoga program for 8 weeks. Measurements were taken using a psychosocial questionnaire before and after the intervention. The results showed a significant improvement in the psychosocial aspects of the elderly, including social interaction, stress reduction, and increased life satisfaction, with a p-value < 0.05. These findings indicate that yoga therapy is effective in enhancing the psychosocial well-being of elderly individuals. This study is expected to contribute to health professionals and program managers by integrating yoga as part of routine activities in posyandu.